A Collision Coupling Model Governs the Activation of Neuronal GIRK1/2 Channels by Muscarinic-2 Receptors - Berlin, Shai; Artzy, Etay; Handklo-Jamal, Reem; Kahanovitch, Uri; Parnas, Hanna; Dascal, Nathan; Yakubovich, Daniel (Frontiers in Pharmacology, 2020)
The G protein-activated Inwardly Rectifying K+-channel (GIRK) modulates heart rate and neuronal excitability. Following G-Protein Coupled Receptor (GPCR)-mediated activation of heterotrimeric G proteins (Gαβγ), opening of the channel is obtained by direct binding of Gβγ subunits. Interestingly, GIRKs are solely activated by Gβγ subunits released from Gαi/o-coupled GPCRs, despite the fact that all receptor types, for instance Gαq-coupled, are also able to provide Gβγ subunits. It is proposed that this specificity and fast kinetics of activation stem from pre-coupling (or pre-assembly) of proteins within this signaling cascade. However, many studies, including our own, point towards a diffusion-limited mechanism, namely collision coupling. Here, we set out to address this long-standing question by combining electrophysiology, imaging and mathematical modeling. Muscarinic-2 receptors (M2R) and neuronal GIRK1/2 channels were coexpressed in Xenopus laevis oocytes, where we monitored protein surface expression, current amplitude and activation kinetics. Densities of expressed M2R were assessed using a fluorescently labeled GIRK channel as a molecular ruler. We then incorporated our results, along with available kinetic data reported for the G-protein cycle and for GIRK1/2 activation, to generate a comprehensive mathematical model for the M2R-G-protein-GIRK1/2 signaling cascade. We find that, without assuming any irreversible interactions, our collision coupling kinetic model faithfully reproduces the rate of channel activation, the changes in agonist-evoked currents and the acceleration of channel activation by increased receptor densities.